Primary subcutaneous extraskeletal Ewing’s sarcoma (PNET). A case report and literatura review - Paucar-Lescano, Patricia K. (2020)
Ewing´s sarcomas are a less common malignant neoplasms that can be located both in skeletal and extra skeletal areas. The primitive neuroectodermic tumor (PNET) shows more neuronal differentiation than Ewing´s sarcoma and rarely invades the skin and soft tissues. This tumor occasionally presents as a primary skin cancer which has distinctive features such as a superficial tumor with a 2-3 cm, soft, mobile and eventually painful. Most affected areas of the body are paravertebral spaces, lower limbs, head, neck and pelvis. We report here the case of a 13 year old male presenting with 2 superficial tumors located on the scalp, the histo pathological examination revealed a proliferation of small, basophilic and monomorphic cells that showed FLI1 positive immunohistochemistry pattern compatible with PNET.